2020
DOI: 10.1007/s11135-020-00974-y
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and poverty in the very poor Peru: measurement improvements and a consistent relationship

Abstract: Despite of poverty and extreme poverty estimations having decreased during the period 2006-2016 in Peru, from 49.1 to 20.7% and from 16.1 to 3.8%, respectively, the poor population still represents a latent concern for policy makers. Essentially, the main reason lies on the multidimensional problems of quality of life. Then, a research question yet unaddressed rises: Is it possible to find very poor people who feel happy? If so, what controls this relationship? The first main contribution of this study is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
3
4
0
5
Order By: Relevance
“…It is found that there is a statistically significant relationship between marital status and happiness in Turkey; married individuals are happier than unmarried. This result is also parallel with the existing literature (Selim, 2008;Mateu et al, 2020). When the relationship between the variable's marital status and the person who makes the individual happiest, it is noted that individuals who never married are happy on their own and with their friends.…”
Section: Figure 2 Graphical Representation Of Centroidssupporting
confidence: 86%
“…It is found that there is a statistically significant relationship between marital status and happiness in Turkey; married individuals are happier than unmarried. This result is also parallel with the existing literature (Selim, 2008;Mateu et al, 2020). When the relationship between the variable's marital status and the person who makes the individual happiest, it is noted that individuals who never married are happy on their own and with their friends.…”
Section: Figure 2 Graphical Representation Of Centroidssupporting
confidence: 86%
“…Luego, estos fueron transformados a una escala de 0 a 20 para facilitar su comprensión, ya que esta es común en la medición de rendimientos escolares del Perú, a diferencia de otros países que utilizan escalas del 1 al 10 o al 100. El cálculo de los puntajes de felicidad se describe en Mateu et al (2020).…”
Section: Religión Y Felicidadunclassified
“…¿Qué se halló respecto de la felicidad? Esta fue calculada a partir de la escala de 0 a 20 (Mateu et al, 2020). Para quienes están en una posición 6…”
Section: Religión Y Felicidadunclassified
“…El promedio de felicidad, calculada a partir de la escala de 0 a 20 (Mateu et al 2020), para quienes están en una posición privilegiada es 14.74, mientras que el promedio para aquellos situados en las antípodas es 11.24 6 . Se trata de una diferencia significativa de más de 3 puntos.…”
Section: Religión Y Felicidadunclassified
“…Estos fueron finalmente transformados a una escala de 0 a 20 para facilitar su comprensión, ya que esta es común en la medición de rendimientos escolares del Perú. El cálculo de los puntajes de felicidad se describe en Mateu et al (2020). Segundo, las preguntas relacionadas a la vivencia religiosa -como importancia concedida a Dios, frecuencia de asistencia a ritos o de meditación y oración-se diseñaron desde la Encuesta Mundial de Valores: 2010-2012 3 .…”
Section: Introductionunclassified